PENGARUH PERSEPSI AUDITOR TERHADAP KINERJA AUDITOR (Studi Empiris pada Auditor Sektor Publik di Inspektorat Kabupaten Serang) - Puspitasari, Devi (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
This study aims to determine and examine the effect of auditor perceptions on auditor  performance in the attack district inspectorate. The object in this study is the inspectorate in the  district government attack. Sampling is done by survey method. The type of data used is subject  data, and the data source used is primary data. Processing and analysis of data using the help of  SPSS vesi 19.00 application with multiple linear regression models. Based on the results of  hypothesis testing obtained Audit Effectiveness has a positive and significant effect on the  performance of public sector auditors, Auditor Policy has a positive and significant effect on the  performance of public sector auditors, External Auditor Professionals have a significant and  positive effect on the performance of public sector auditors, Other Expert Professionals have a  positive and significant effect on public sector auditor performance, barriers have a positive and  significant effect on the performance of public sector auditors, Public Administration has a  positive effect on the performance of public sector auditors.